Effect of calcium reduction on the properties of half-fat Cheddar-style cheeses with full-salt or half-salt. (October 2017) - McCarthy, Catherine M.; Wilkinson, Martin G.; Guinee, Timothy P.
Abstract: Standard-calcium (SCa) and reduced-calcium (RCa) half-fat (16%) Cheddar-style cheeses with full-salt (1.9%) or half-salt (0.9%) were made in triplicate, ripened for 270 d, and analysed for composition and changes in lactose metabolism, pH, proteolysis, water-sorption, fracture properties and heat-induced flowability during maturation. The pressing load applied to the moulded cheese was modified to ensure equal moisture in all cheeses despite the differences in salt and calcium levels. The RCa cheeses were characterised by higher primary proteolysis (αS1 -casein degradation, pH 4.6-soluble N development), lower secondary proteolysis (concentration of free amino acids), higher water-holding capacity on reducing relative humidity from 85 to 5%, lower fracture stress and strain, and more extensive flow on heating. Overall, calcium reduction, when used in conjunction with moisture normalisation, proved an effective means of counteracting the adverse effects of fat reduction on texture and cooking properties in half-fat, half-salt cheese.